PERLINDUNGAN KONSUMEN TERHADAP PERBUATAN MELAWAN HUKUM OLEH DEVELOPER PERUMAHAN DALAM MELAKUKAN PEMASARAN - Bella Destya Handayanti; Dhany Rahmawan (Fakultas Hukum Universitas Trisakti, 2022)
In order to attract consumer interest, sometimes the marketing of a product provides excessive information about the product, for example, marketing in the property sector, which provides information that is not in accordance with the facts. The formulation of the research problem is how is the legal protection of housing consumers and whether consumers who are harmed can file a claim for compensation to the developer. This research is a literature study, the nature of the research is descriptive. The results of the research are as follows, namely that there are several regulations regarding consumer protection regulated in the Housing Law; Consumer Protection Act; Government Regulation Number 58 of 2001 concerning Guidance and Supervision of the Implementation of Consumer Protection; Minister of Home Affairs Regulation Number 69 of 2018 concerning Supervision of Circulating Goods and/or Services. And in this case consumers who feel aggrieved can file a lawsuit for compensation based on Article 45 of the UUPK, and Article 148 of the PKP Law.